Characteristics and Effects of Multiple and Mixed Funding Flows to Public Healthcare Facilities on Financing Outcomes: A Case Study From Nigeria - Onwujekwe, Obinna; Mbachu, Chinyere; Ezenwaka, Uche; Arize, Ifeyinwa; Ezumah, Nkoli (Frontiers in Public Health, 2020)
Introduction: Most public hospitals in Nigeria are usually financed by funding flows from different health financing mechanisms, which could potentially trigger different provider behaviors that can affect the health system goals of efficiency, equity, and quality of care. The study examined how healthcare providers respond to multiple funding flows and the implications of such flows for achieving equity, efficiency, and quality. Methods: A cross-sectional qualitative study of selected healthcare providers and purchasers in Enugu state was used. Four public hospitals were selected—two tertiary and two secondary; because they received funding from more than one healthcare financing mechanism. Key informants were individual healthcare providers and decision-makers in the hospitals, State Ministry of Health, National Health Insurance Scheme and Health Maintenance Organizations. Service users from each hospital were purposively selected for focus group discussions (FGDs). A total of 66 key informant interviews and 8 FGDs were conducted. Findings: The multiple flows that were received by public hospitals varied by type of health facility (Secondary vs. Tertiary), ownership of health facility (Federal government vs. State government) and population served. Out-of-pocket payment (OOP) and government budget were the only recurring forms of funding to all the public hospitals. It was found that multiple funding flows, generate different signals to service providers, resulting in positive and negative consequences. The results also showed that multiple flows lead to predictability and stability of funding to public hospitals. Hospital Managers and administrators reported that multiple flows increased their financial pool and capacity to undertake capital projects and enabled the provision of a wider range of services to clients. Multiple sources of funding also give a sense of security to health facilities, because there would always be a back-up source of funding if one flow delays or defaults in payment. Nevertheless, health providers were seen to shift resources from less attractive to more attractive flows in response to the relative size perceived adequacy, predictability, and flexibility of funding flow. Patients were also shifted from less predictable to more predictable funding flows and providers charged different rates to different funding flows to make up for the inadequacies in some sources of funding. The negative consequences of multiple funding flows on provider behavior that was reported in the study were wastage/under-utilization of resources, differential quality of care provided to clients, and inequities in resource distribution and access to health services. In some instances, providers' responses resulted in better quality of care for clients and improved access to services that were not ordinarily available or clients could not have been afforded. Conclusion: Multiple funding flows to public hospitals are beneficial as well as constraining to health providers. They can be beneficial in ensuring that hospitals have a ready and predictable pool of funds to render services with. However, they could be detrimental to some patients that could be charged more for some services that other patients pay less and may also lead of provision of differential quality of services to different payments depending on the funding flows that are used to purchase services for them. Ultimately, some of the consequences of multiple funding flows if not properly managed, will affect health systems goals of equity, efficiency and quality of care, either positively or negatively.